The effect of multi-pass friction stir processing on microstructure and mechanical properties of dual-phase brass alloy - M. Khalili; A.R. Eivani; S.H. Seyedein; H.R. Jafarian (Journal of Materials Research and Technology, 2022)
This research aims to improve the microstructure and mechanical properties of C38000 brass alloy by multi-pass friction stir processing (MPFSP). In this study, The MPFSP was carried out on a dual-phase brass alloy sheet with a thickness of 5 mm at fully annealed conditions. To determine the effect of the number of passes on microstructure and mechanical properties of this alloy, rotational and traverse speeds were chosen at 750 rpm and 100 mm∖min, respectively. This process was performed in 1, 2, 4, and 6 passes. Metallography, microhardness, tensile, wear, and fractography are tests done to investigate the changes in microstructure and mechanical properties after processing. Finally, the relation between the microstructural and mechanical properties of MPFSPed specimens was discussed. Studying the tests mentioned above resulted that the MPFSP has caused a decrease in the grain size of the matrix and second phase (β′) particles. Furthermore, mechanical properties such as yield strength, ultimate tensile strength, and hardness were enhanced. It was obtained that elongation to failure has a decreasing trend with increasing the number of FSP passes. Tribological behaviors were also improved after performing MPFSP. The levels of grain size refining and improving the mechanical properties are directly related to increasing the number of passes. However, after performing six passes of FSP, there was no significant change in the microstructure and mechanical properties in comparison to that after 4 passes of FSP. The properties of 4 and 6 passes FSPed specimens showed that these had the most refined microstructures and enhanced mechanical properties with remarkable elongation.